Book Review: Peremptory International Law Jus Cogens - A General Inventory by Robert Colb - Handayani, Irawati (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
Book Review: Peremptory International Law Jus Cogens - A General Inventory by Robert Colb